Milton and the idea of the fall - Poole, William, 1977- (Cambridge University Press, 2005)
In Paradise Lost (1667), Milton produced the most magnificent poetic account ever written of the biblical Fall of man. In this wide-ranging study, William Poole analyses the origin, evolution, and contemporary discussion of the Fall, and offers many new insights into the originality and sophistication of Milton's work.